THE EVOLUTION OF THE B-FUTURE MARKER IN SYRIAN ARABIC - Jarad, Najib Ismail (Lingua Posnaniensis, 2013)
The formation of future markers from distinct lexical sources or from similar sources under specific circumstances follows universal pathways. It is standardly agreed that grammaticalization is a process which encompasses a range of changes which involve desemanticization (loss of meaning), decategorialization (loss of categorical features), generalization (use extended to new contexts), and phonetic reduction. The paper assumes that the b-prefix derives from two distinct lexical sources: volitional (encoding future) and prepositional (encoding indicative mood, progressive, and habitual aspect), and that the morphological overlap of these two prefixes is a mere coincidence. The paper will concentrate on the development of the future marker (b-prefix) from a verbal noun of volition in Syrian Arabic. The main goal is to explicate the nature of the grammaticalization paths of the b-future in Syrian Arabic based on synchronic data. The paper posits that the verbal noun of volition has undergone semantic, structural, and phonological changes.